Knowledge management - M. Tayfun Gülle (Türk Kütüphaneciliği)
The book includes detailed information concerning knowledge and knowledge management with current resources in seven chapters uder the titles of “organizational effects of knowlegde management, knowledge management systems, new knowledge discovery: data mining, computer as an information sharing platform, technologies as knowledge management: artificial intelligence and knowledge based systems, future of knowlegde management”. Concepts of knowledge and knowledge management becomes phenomenon for all disciplinaries so global companies, other companies, state sector, epistemologists, experts of innovation and governance, information professionals etc may find informative to it. The book also includes three prefaces which are well-informed and so all of them is summarized in the text.